Association of human leukocyte antigen and T cell message with human papillomavirus 16–positive cervical neoplasia in Japanese women. Issue 6 (1st October 2007) - Saito, M.; Okubo, M.; Hirata, R.; Takeda, S.; Maeda, H.
Abstract : To investigate whether an association exists between human leukocyte antigen (HLA) haplotype and cervical neoplasia within the Japanese population, we analyzed the human papillomavirus (HPV) genotypes, the HLA class I specificities and class II alleles, and the T-cell responses in the lesions of patients with cervical neoplasia. Eighty-one patients, consisting of 62 cervical intraepithelial neoplasia (CIN) lesions and 19 invasive cervical cancers (ICC), were examined. The frequencies of HPV infection in the CIN I/II and CIN III/ICC groups were 68.0% (17/25) and 80.4% (45/56), respectively. All patients and 138 local Japanese controls were analyzed for HLA-A, HLA-B, HLA-DRB1, and HLA-DQB1. For major histocompatibility complex (MHC) class II HLA-DRB1 alleles, the frequency of DRB1*0901 was significantly elevated in HPV 16–positive CIN III/ICC patients compared with controls (59.3% versus 29.7%, P = 0.0031, OR = 3.44). Similarly for the HLA-DQB1 alleles, a significant increase in the DQB1*03032 frequency was observed in HPV 16–positive CIN III/ICC patients compared with controls (59.3% versus 28.3%, P = 0.0018, OR = 3.69). In the analysis of the T-cell responses in the lesions, Fas ligand was detected at a decreased frequency in HPV 16–positive CIN III/ICC patients with the HLA-DRB1*0901–DQB1*03032 haplotype. The presence of helper T cell–specific messenger RNAs in the cervical lesions supports an association among MHC class II, helper T cells, the immune response to HPV, and the development of cervical carcinoma. Accordingly, a specific MHC class II haplotype, DRB1*0901–DQB1*03032, may be a risk factor for cervical carcinoma in the Japanese population.